BETWEEN THE PRESERVATION OF FREEDOM AND RATIONALITY: ANALYSES BY JOHN DEWEY AND HERBERT MARCUSE - Centenaro, Angela Ester Mallmann (Seven Editora, 2025)
This article aims to present, starting from Chapter 1 (The Problem of Liberty) of one of Dewey’s works entitled "Liberalism, Liberty and Culture," where he uses the idea of ​​liberty to arrive at two basic questions: first, the tension he exposes throughout, between the foundations of liberty and its preservation. And second, the idea of ​​the principles or possible relationships between liberty and social cohesion or solidarity, which are the issues at stake in the first two paragraphs of the text, grouping several questions around these references. In the second part of the work, we analyze the introduction and Chapter 1 of Herbert Marcuse’s work "The Ideology of Industrial Society." For Marcuse, modern industrial society imposes a technological rationality of mass domination and oppression, of control over human consciousness. The man who finds himself inserted in the society of artificiality is not free; on the contrary, he is an automaton, incapable of opposing the system of the technological apparatus. There is a satisfaction of false needs, which causes the so-called "mechanics of conformity." This paper seeks to reproduce and reflect upon the critical social theory developed by Marcuse regarding the new ideology of advanced technological society. DOI: https://doi.org/10.56238/sevened2025.036-133